1993
DOI: 10.1038/hdy.1993.162
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and distribution of variation in degree of copper tolerance in Mimulus guttatus at Copperopolis, California

Abstract: The variation in degree of copper tolerance, its heritability and relationship with copper contamination of the soil and geographical location of sample, was studied on samples of seed collected from a large abandoned copper mine at Copperopolis, California. The realized heritability of variation in degree of tolerance at a high level of copper, 2 1ug cm , is shown to be about 0.40. The F1s of crosses between an upward and downward selection line and a non-tolerant line give intermediate values for tolerance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 32 publications
4
66
0
Order By: Relevance
“…Populations from uncontaminated sites were slightly less Zn tolerant than those from contaminated sites. If the first hypothesis were true, this would suggest that some of the modifiers of tolerance have been lost, either through selection, if they have some cost (as postulated by Macnair et al, 1993, for coppertolerance modifiers), or mutation and drift if they are neutral in an uncontaminated environment. By contrast, hypothesis 2 suggests that the species was pre-adapted to colonize Zn-contaminated sites.…”
Section: Origin and Evolution Of Constitutive Tolerance And Hyperaccumentioning
confidence: 99%
“…Populations from uncontaminated sites were slightly less Zn tolerant than those from contaminated sites. If the first hypothesis were true, this would suggest that some of the modifiers of tolerance have been lost, either through selection, if they have some cost (as postulated by Macnair et al, 1993, for coppertolerance modifiers), or mutation and drift if they are neutral in an uncontaminated environment. By contrast, hypothesis 2 suggests that the species was pre-adapted to colonize Zn-contaminated sites.…”
Section: Origin and Evolution Of Constitutive Tolerance And Hyperaccumentioning
confidence: 99%
“…All selection lines were grown and raised as in Macnair et al (1993). Ten cuttings from each line were harvested at between 5 and 15 cm height and were then tested at 0.0, 0.5, 1.0, 1.5 and 2.0 pg cm3 Cd, and 0.0, 0.5, 1.0, 2.0 and 3.0 pg cm3 Cu, with calcium nitrate addition at 0.5 g L'.…”
Section: Methodsologymentioning
confidence: 99%
“…Each pair of lines was selected both for increased (H line) and decreased (L line) tolerance. Three pairs of lines were derived from Copperopolis (see Allen & Sheppard, 1971;Macnair et al, 1993). The first, which had been selected for six generations (H(, and L6), had originally been established from pooled seed from the whole of the mine.…”
Section: Modifiers Of Copper Tolerancementioning
confidence: 99%
“…They are often endemic to few small areas of metalliferous soils; some are known from only a single site or have been collected in only few occasions (e.g., , Malaisse et al 1994, Léteinturier et al 2001. Some are adapted variants (ecotypes) of common species (pseudometallophytes), such as Deschampsia caespitosa (Cox & Hutchinson 1980, Bush & Barret 1993, Holcus lanatus (Baker 1984), and Mimulus gutattus (Allen & Sheppard 1971, Macnair et al 1993, and can be found widely over metal-rich environments. Others, however, are species strictly restricted to their particular metallogenic provinces, such as some Becium species, that only grow on isolated natural copper outcrops in the Democratic Republic of Congo (formerly Zaire), central Africa (Brooks et al 1992a).…”
Section: Introductionmentioning
confidence: 99%
“…Metal tolerance in higher plants has been traditionally assessed through standardized laboratory tests by determining the effect of metal ions on root elongation (e.g., Baker & Walker 1989, Lambers et al 1998. Using this methodology, numerous studies have identified and quantified metal tolerance for copper, cadmium, iron, manganese, nickel, lead, and zinc in several higher plants (e.g., Allen & Sheppard 1971, Hogan et al 1977, Baker & Brooks 1989, Macnair et al 1993, Ginocchio et al 2002.…”
Section: Introductionmentioning
confidence: 99%